The effects of blurred visual inputs with different levels on the cerebral activity during free level walking - Ao, Mingxin; Ren, Shuang; Yu, Yuanyuan; Huang, Hongshi; Miao, Xin; Ao, Yingfang; Wang, Wei (Frontiers in Neuroscience, 2023)
Objective: To evaluate the effects of blurred vision with different levels on electrocortical activities during walking. Materials and methods: Twenty-two healthy volunteers (all males; mean age: 24.4±3.9 yrs.) underwent electroencephalography (EEG) test synchronous with free level walking. Visual status was simulated by goggles covered by occlusion foil targeted at Snellen visual acuity of 20/60 (V0.3), 20/200 (V0.1) and light perception (V0). At each condition, the participants completed five barefoot walking blocks of 10 meters. EEG signals were recorded by wireless EEG system with interested electrodes of Cz, Pz, Oz, O1 and O2. Gait performances were assessed by Vicon system. Results: During walking with normal vision (V1.0), there were cerebral activities related to visual processing, characterized as higher spectral power of delta (Oz and O2 vs Cz, Pz, and O1, P≤0.033) and theta (Oz vs Cz and O1, P=0.044) bands in occipital regions. Moderately blurred vision (V0.3) would attenuate the predominance of delta and theta bands activity at Oz and O2. At status of V0.1 and V0, the higher power of delta (at V0.1 and V0, Oz and O2 vs Cz, Pz, and O1, P≤0.047) and theta bands (at V0.1, Oz vs Cz, P=0.010; at V0, Oz vs Cz, Pz, and O1, P≤0.016) emerged again. The cautious gait pattern, characterized as decrease of gait speed (P＜0.001), greater amplitude of deviation from the right ahead (P＜0.001), prolonged stance time (P=0.001), restricted range of motion in hip on the right side (P≤0.010) and increased knee flexion during stance on the left side (P=0.014), was only detected at the status of V0. The power of alpha band at the status of V0 was higher than that at V1.0, V0.3 and V0.1 (P≤0.011). Conclusion: Mildly blurred visual input would elicit generalization of low frequency bands activity during walking. In response to severe visual interference, the locomotor navigation would rely on cerebral activity related to visual working memory, threshold of which to trigger the shift might be the visual status as blurred as the level of Snellen visual acuity of 20/200.